2006
DOI: 10.5194/acpd-6-9603-2006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nucleation and growth of new particles in Po Valley, Italy

Abstract: Abstract. Aerosol number distribution measurements are reported at San Pietro Capofiume (SPC) station (44°39' N, 11°37' E) for the time period 2002–2005. The station is located in Po Valley, the largest industrial, trading and agricultural area in Italy with a high population density. New particle formation was studied based on observations of the particle size distribution, meteorological and gas phase parameters. The nucleation events were classified according to the event clarity based on the particle numbe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 36 publications
2
46
0
Order By: Relevance
“…If we compare the observations with measurements carried out in other sites (see Kulmala et al, 2004, and references therein) as well as recent study from Po-valley, Italy (Hameed et al, 2007) we notice that the frequency of the new-particles formation events, as also the particle formation and growth rates, are among the highest observed in continental areas. Other important difference is the any lack of seasonal variability -clearly, we have enough nucleating and condensing vapors as well as solar radiation for nucleation to take place throughout the year.…”
Section: Correlationsmentioning
confidence: 91%
“…If we compare the observations with measurements carried out in other sites (see Kulmala et al, 2004, and references therein) as well as recent study from Po-valley, Italy (Hameed et al, 2007) we notice that the frequency of the new-particles formation events, as also the particle formation and growth rates, are among the highest observed in continental areas. Other important difference is the any lack of seasonal variability -clearly, we have enough nucleating and condensing vapors as well as solar radiation for nucleation to take place throughout the year.…”
Section: Correlationsmentioning
confidence: 91%
“…In this area, the high anthropogenic pressure combined with peculiar weather conditions favor pollutant accumulation and nucleation events (e.g. Hamed et al, 2007;Squizzato et al, 2013), which are mainly responsible for the highest levels observed for many atmospheric pollutants (EEA, 2013).…”
Section: Study Areamentioning
confidence: 99%
“…The concentrations and formation mechanisms of PM 2.5 and SIA were already studied in some sites of Po Valley such as San Pietro Capofiume (Boulogne), Milan, Venice Lagoon (see e.g., Hamed et al, 2007;Sogacheva et al, 2007;Lonati et al, 2008;Prodi et al, 2009), but relatively scarce data are available for the Eastern part of the Po plain. In particular only few studies reported on air quality in the Venice-Mestre area (Rampazzo et al, 2008a(Rampazzo et al, , 2008bStortini et al, 2009;Masiol et al, 2010) and mainly discussed element characterization, source identification and apportionment.…”
Section: Introductionmentioning
confidence: 99%